DADU SICHERMAN - Nurlaelah, Elah (Jurnal Pengajaran MIPA, 2001)
An interesting application of unique factorization in Z[X] is Sicherman dice.Â  The dice is a pair of dice whose has different number from ordinary dice which faces are labeled 1 through 6. But probability the sumÂ  of faces are same as the sum of ordinary dices. Sicherman dice is obtained by using one to one correspondence between the two polynomials and the face of two dice of ordinary dice.